Evaluation as a mechanism of the regulation of academic work. Case studies at universities in Argentina and Spain - Walker, Verónica Soledad (Education Policy Analysis Archives, 2017)
This article focuses on evaluation as a mechanism for regulation within the university field and its impact on academic work. An analysis, based on the literature and data obtained in an investigation that addressed policy evaluation of teaching in Argentina and Spain, reveals that assessment processes propitiate forms of organization of academic work characterized by individualism, strategic actions, simulation, competition, bureaucratization, and stress. The article proposes that assessment is an instrument of subjectivity that shapes particular ways of inhabiting the university.